Conjugate heat transfer analysis of the tip seal in the counter rotating low pressure turbine - Bochon, K.; Wróblewski, W. (Archives of Mechanics, 2015)
The aim of this study was to examine the phenomena associated with leakage flow through the tip seal with honeycomb land and to perform conjugate heat transfer (CHT) analysis of the entire tip area of the blade including the part of casing with rotating cavity above the seal. CFD analyses were performed using commercial software. For the complicated geometrical configuration of the seal region, a calculation model was proposed which enabled a satisfactory approach to flow and heat transfer phenomena. CHT analyses were performed for two cases characterized by different thermal conductivity of the metal. Fluid flow parameters which allowed to recognize flow structures, losses and mixing were taken into account. In CHT analyses, the flow structures for the cavity, the heat transfer conditions as well as the temperature distribution in the whole domain were obtained.